2009 Swine-origin influenza A (H1N1) resembles previous influenza isolates. - Carl Kingsford; Niranjan Nagarajan; Steven L Salzberg (PLoS ONE)
Background In April 2009, novel swine-origin influenza viruses (S-OIV) were identified in patients from Mexico and the United States. The viruses were genetically characterized as a novel influenza A (H1N1) strain originating in swine, and within a very short time the S-OIV strain spread across the globe via human-to-human contact. Methodology We conducted a comprehensive computational search of all available sequences of the surface proteins of H1N1 swine influenza isolates and found that a similar strain to S-OIV appeared in Thailand in 2000. The earlier isolates caused infections in pigs but only one sequenced human case, A/Thailand/271/2005 (H1N1). Significance Differences between the Thai cases and S-OIV may help shed light on the ability of the current outbreak strain to spread rapidly among humans.